Efectividad del programa educativo en el conocimiento materno del cuidado del niño con asma - 2016 - Maco Crispin, Sharon (2016)
This investigation quantitative type, experimental pre, was held at the Tomas La Fora De Guadalupe Hospital, in 93 mothers of children who suffer from asthma, in September and October 2016, in order to determine the effectiveness of the educational program "Helping to Breathe My child "in the knowledge of mothers about the care of children with asthma. the instrument was used for data collection: Survey to determine the maternal knowledge of child care with asthma; being processed and analyzed by Chi Square test information obtained, the results are presented in tables simple, double entry; after analysis was reached the following conclusions: Before the implementation of the educational program 45 percent of mothers had average knowledge level, 38 percent under and 17 percent, high after of the implementation of educational programs a 68 percent average knowledge obtained, 32 percent higher. The educational program was highly significant to increase by 95% the maternal knowledge of child care with asthma